Causal association between self-reported fatigue and coronary artery disease: a bidirectional two-sample Mendelian randomization analysis - Qi, Xiaoyi; Wang, Shijia; Qiu, Liangxian; Chen, Xiongbiao; Huang, Qianwen; Ouyang, Kunfu; Chen, Yanjun (Frontiers in Psychiatry, 2023)
Background: Observational studies have reported the association between fatigue and coronary artery disease (CAD), but the causal association between fatigue and CAD is unclear.We conducted a bidirectional Mendelian randomization (MR) study using publicly available genome-wide association studies (GWAS) data. The inverse-variance weighted (IVW) method was used as the primary analysis. We performed three complementary methods, including weighted median, MR-Egger regression, and MR pleiotropy residual sum and outlier (MR-PRESSO) to evaluate the sensitivity and horizontal pleiotropy of the results.Result: Self-reported fatigue had a causal effect on coronary artery atherosclerosis (CAA) (OR 1.047, 95%CI 1.033-1.062), myocardial infarction (MI) (OR 1.027 95%CI 1.014-1.039) and coronary heart disease (CHD) (OR 1.037, 95%CI 1.021-1.053). We did not find a significant reverse causality between self-reported fatigue and CAD. Given the heterogeneity revealed by MR-Egger regression, we employed the IVW random effect model. For the examination of fatigue on CHD and the reverse analysis of CAA, and MI on fatigue, the MR-PRESSO test found horizontal pleiotropy. No significant outliers were found.The MR analysis reveals a causal relationship between self-reported fatigue and CAD. The results should be interpreted with caution due to horizontal pleiotropy.